One more cup of coffee for the road: object-action assemblies, response blocking and response capture after frontal lobe damage. - Humphreys, G; Riddoch, M (2000)
We report data from a patient, FK, who manifested 'utilisation' behaviour after bilateral lesions of the medial frontal and anterior temporal lobes. In tasks requiring actions to be made with the hand compatible with the orientation of a cup, FK was able to ignore irrelevant distractors that fell in the path of action to the target. However, errors were made when the distractors were other cups. These errors reflected the hand selected on the basis of the properties of the target, suggesting that distractors competed to control the action after selection of the target. When similar in kind to the target, distractors sometimes captured the action. However, distractors that were associated with an action related to the target blocked the usual hand response. These results suggest a complex interlocking of attention and action when grasping responses are made to a target amongst distractors. There is initial selection of the target, but distractors on the path of a reach can then compete for control of the action. Distractors can be inhibited if they do not match the properties of the specified target, and there can also be inhibition of concurrently activated responses. We show that the magnitude of the inhibition is proportional to the strength of learned object-action associations.